Hemodialysis Does Not Induce Detectable Activation of the Contact System of Coagulation - François, Karlien (Kidney Int Rep, 2020)
INTRODUCTION: Systemic anticoagulation is administered during hemodialysis to prevent clotting of the extracorporeal circuit. The role of contact system activation in thrombin generation during hemodialysis using current era dialyzer membranes is unknown. METHODS: We performed a single-center randomized crossover study. Ten patients treated with hemodialysis underwent 3 standardized hemodialysis sessions. For every patient, each session was performed with a different type of dialyzer membrane (polyphenylene [PP], polymethylmetacrylate [PMMA], polyethylenimine-coated polyacrylonitrile [AN69ST]). Blood samples were collected before and 5, 15, 30, 90, and 240 minutes after blood pump start to evaluate coagulation activation (thrombin–antithrombin complex [TAT], prothrombin fragment 1+2 [PF1+2], activated factor XII [FXIIa], kallikrein, activated factor XI [FXIa]). Plasma of healthy volunteers (n = 20) was used as a reference. RESULTS: Baseline TAT and PF1+2 levels were higher in hemodialysis patients compared to healthy controls (median [interquartile range] for TAT: 3.3 [2.9–4.2] vs. 2.4 [2.3–2.5] μg/l [P = 0.0002] and for PF1+2: 647 [478–737] vs. 138 [125–254] pmol/l [P < 0.0002]). Despite the use of systemic anticoagulation, TAT further increased during treatment, with the increase starting after 30 minutes (median TAT at t240: 9.0 μg/l (PP), 5.5 μg/l (PMMA), and 7.2 μg/l (AN69ST), all P < 0.05 vs. baseline). Contact system markers FXIIa and kallikrein did not differ significantly between dialysis patients and healthy controls, whereas baseline FXIa levels were significantly lower in dialysis patients compared to healthy controls (P = 0.001). Levels of all contact system markers remained unchanged during hemodialysis with all types of dialyzer membranes. CONCLUSION: Routine hemodialysis using systemic heparin anticoagulation induces coagulation activation without measurable contact system activation.